The Global Response of Cronobacter sakazakii Cells to Amino Acid Deficiency - Chen, Si; Zhou, Qing; Tan, Xin; Li, Ye; Ren, Ge; Wang, Xiaoyuan (Frontiers in Microbiology, 2018)
Cronobacter species can cause necrotizing enterocolitis and meningitis in neonates and infants, their infection is closely relevant to their responses to extreme growth conditions. In this study, the response of Cronobacter species to amino acid deficiency has been investigated. Four Cronobacter species formed smooth colonies when grown on the solid LB medium, but formed mucoid colonies when grown on the amino acid deficient M9 medium. When the mucoid colonies were stained with tannin mordant, exopolysaccharide around the cells could be discerned. The exopolysaccharide was isolated, analyzed, and identified as colanic acid. When genes wcaD and wcaE relevant to colanic acid biosynthesis were deleted in C. sakazakii BAA-894, no exopolysaccharide could be produced, confirming the exopolysaccharide formed in C. sakazakii grown in M9 is colanic acid. On the other hand, when genes rcsA, rcsB, rcsC, rcsD, or rcsF relevant to Rcs phosphorelay system was deleted in C. sakazakii BAA-894, colanic acid could not be produced, suggesting that the production of colanic acid in C. sakazakii is regulated by Rcs phosphorelay system. Furthermore, C. sakazakii BAA-894 grown in M9 supplemented with amino acids could not produce exopolysaccharide. Transcriptomes of C. sakazakii BAA-894 grown in M9 or LB were analyzed. A total of 3956 genes were differentially expressed in M9, of which 2339 were up-regulated and 1617 were down-regulated. When C. sakazakii BAA-894 was grown in M9, the genes relevant to the biosynthesis of exopolysaccharide were significantly up-regulated; on the other hand, the genes relevant to the flagellum formation and chemotaxis were significantly down-regulated; in addition, most genes relevant to various amino acid biosynthesis were also significantly regulated. The results demonstrate that amino acid deficiency has a global impact on C. sakazakii cells.